Retrospective Risk Assessment of Injuries and Fatalities in the Forestry and Logging Workforce in the United States, 2003-2019 - Heidi Knecht; Jo Anne G Balanay; Ricky Langley; Robin Tutor Marcom; Stephanie L. Richards (Journal of Agromedicine, 2024)

Systematic Review of Biological, Chemical, Ergonomic, Physical, and Psychosocial Hazards Impacting Occupational Health of United States Forestry Workers - Heidi Knecht; Jo Anne G Balanay; Ricky Langley; Robin Tutor Marcom; Stephanie L Richards (Journal of Forestry, 2024)
Forestry is one of the most hazardous occupations, due in part to the biological, chemical, ergonomic, physical, and psychosocial aspects of the job. Here, we review health risks in forestry occupations, including those in professional and technical forestry, logging, and forestry support, from the standpoint of biological (e.g., insects/arachnids, plants), chemical (e.g., diesel exhaust), ergonomic (e.g., awkward postures, forceful motions), physical (temperature, noise, vibrations, radiation), and psychosocial (e.g., workplace factors that cause stress, strain, or interpersonal problems for the worker) issues. We conducted a systematic review over a 10-year period (2011–2021) to assess health hazards identified in studies conducted on these occupations and reveal knowledge gaps for future studies to address. This study focuses on occupational health rather than occupational safety. Other forestry worker occupational health and safety studies have focused on analyzing injuries and deaths directly relating to transportation and/or contact with objects such as trees or logs and equipment; however, the areas of occupational health highlighted here have been understudied. Future work should focus on these areas, with an emphasis on intervention strategies that eliminate or mitigate the deleterious health effects of occupational exposures. Study Implications: Forestry workers are exposed to occupational health hazards in their outdoor workplace. This review analyzes published work for a 10-year period (2011–2021) with broader implications such as (1) greater understanding of gaps in the literature for key occupational health hazards facing United States forestry workers and (2) better information on the need for more in-depth studies to collect information about exposure assessments to improve worker protection. This literature review can help forestry workers, managers, and scientists mitigate exposures and protect health.

Working along the Continuum: North Carolina’s Collaborative Response to COVID-19 for Migrant & Seasonal Farmworkers - Robin Tutor Marcom; Elizabeth Freeman Lambar; Beth Rodman; Gayle Thomas; Ann Watson; Bryan Parrish; Jessica Wilburn (Journal of Agromedicine, 2020)

Adapting Certified Safe Farm to North Carolina Agriculture: An Implementation Study - Julia F. Storm; Catherine E. LePrevost; Robin Tutor-Marcom; W. Gregory Cope (Journal of Agromedicine, 2016)

North Carolina Farm Women: Opportunities for Support and Farm-Related Education - Robin Tutor-Marcom; Jacklyn Bruce; Annette Greer (Journal of Agromedicine, 2014)

Not Just the Farm Wife: Perceptions and Needs of North Carolina Farm Women - Robin Tutor-Marcom; Jacklyn Bruce; Annette Greer (Journal of Agromedicine, 2014)

Sustaining Respiratory Protection Through North Carolina’s Risk Mitigation Measures Project - Robin Tutor-Marcom; Fred Wright (Journal of Agromedicine, 2014)

Respiratory Assessment and Use of PPE Among Poultry Workers in NC: A Pilot Study - Gregory D. Kearney; Robert Shaw; Robin Tutor-Marcom; Matthew A. Prentice (Journal of Agromedicine, 2014)

Evaluation of Respiratory Symptoms and Respiratory Protection Behavior Among Poultry Workers in Small Farming Operations - Gregory D. Kearney; Robert Shaw; Matthew Prentice; Robin Tutor-Marcom (Journal of Agromedicine, 2014)

Qualitative Assessment of Agritourism Safety Guidelines: A Demonstration Project - Robin Tutor-Marcom; Annette Greer; Maria Clay; Tammy Ellis; Tami Thompson; Esther Seisay Adam-Samura (Journal of Agromedicine, 2013)

Assessment of Sun Safety Behavior among Farmers Attending a Regional Farm Show in North Carolina - Gregory D. Kearney; C. Suzanne Lea; JoAnne Balanay; Qiang Wu; Jeffrey W. Bethel; Hayley Von Hollen; Kathy Sheppard; Robin Tutor-Marcom; Jennifer Defazio (Journal of Agromedicine, 2013)